Microexpressions Differentiate Truths From Lies About Future Malicious Intent - Matsumoto, David; Hwang, Hyisung C. (Frontiers in Psychology, 2018)
The few previous studies testing whether or not microexpressions are indicators of deception have produced equivocal findings, which may have resulted from restrictive operationalizations of microexpression duration. In this study, we coded facial expressions of emotion produced by community participants in an initial screening interview in a mock crime experiment. The expressions were coded for occurrence and duration and various durations were tested concerning whether their occurrence differentiated between truthtellers and liars concerning their intent to commit a malicious act in the future. We operationalized microexpressions as expressions occurring less than the duration of spontaneously occurring, non-concealed, non-repressed facial expressions of emotion based on empirically documented findings, that is < .50 s, and then more systematically < .40, < .30, and < .20 s. We also compared expressions occurring between .50 – 6.00 s and all expressions < 6.00 s. Results indicated that microexpressions of negative emotions occurring < .40 and < .50 s differentiated truthtellers and liars. Expressions of negative emotions occurring < 6.00 s also differentiated truthtellers from liars but this finding did not survive when expressions < 1.00 s were filtered from the data. These findings provided the first systematic evidence for the existence of microexpressions at various durations and their possible ability to differentiate truthtellers from liars about their intent to commit an act of malfeasance in the future.